2015
DOI: 10.1002/2015gl064081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of snow accumulation on CryoSat‐2 range retrievals over Arctic sea ice: An observational approach with buoy data

Abstract: Radar altimetry measurements of the current satellite mission CryoSat‐2 show an increase of Arctic sea ice thickness in autumn 2013, compared to previous years but also related to March 2013. Such an increase over the melting season seems unlikely and needs to be investigated. Recent studies show that the influence of the snow cover is not negligible and can highly affect the CryoSat‐2 range retrievals if it is assumed that the main scattering horizon is given by the snow‐ice interface. Our analysis of Arctic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 31 publications
4
73
0
Order By: Relevance
“…summer-winter, may change slightly with the form of the retracker, e.g. Ricker et al (2015) showed some influence of the form of the retracker on sea ice freeboard results, we suspect that any CS2-detected elevation will be more dependent on the changing conditions than on the detailed form of the retracker.…”
Section: Discussionmentioning
confidence: 91%
“…summer-winter, may change slightly with the form of the retracker, e.g. Ricker et al (2015) showed some influence of the form of the retracker on sea ice freeboard results, we suspect that any CS2-detected elevation will be more dependent on the changing conditions than on the detailed form of the retracker.…”
Section: Discussionmentioning
confidence: 91%
“…Snow depth is also a requirement for altimetry-based retrieval of sea ice properties (e.g., ice thickness), whereby inadequate knowledge of snow depth distribution directly impacts the availability and quality of derived products [Giles et al, 2007;Kern et al, 2015;Ricker et al, 2015]. Despite its broad importance, remotely sensed estimates of snow depth on sea ice have previously only been available from coarse resolution passive microwave data [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the effect of deformed sea ice on the freeboard and to reduce noise, we calculate modal CS2 freeboard for the relevant grid cells. The modal value is retrieved by fitting a log-normal function to the freeboard distribution of a grid cell and picking the value at the probability maximum [11]. The CS2 freeboard itself is retrieved according to Section 2.2.1.…”
Section: Airborne Laser Scanner Data and Coincident Cryosat-2 Freeboardmentioning
confidence: 99%
“…One source of the high scattering are the different scales of the footprint. While CS2 has a footprint of approximately 300 × 1650 m, the ALS provides a spatial resolution in the range of centimeters and a swath width in the range of ∼100 m. Another source of discrepancy is the fact that the ALS scans the snow surface, while the CS2 radar penetrates into the snow, potentially scattered by internal layers [11,12]. Although we carefully supervise the ALS modal freeboard, it also contains interpolation errors in the instantaneous sea surface height, despite the potentially more accurate lead detection compared to CS2.…”
Section: Comparison With Coincident Airborne Laser Scanner Measurementsmentioning
confidence: 99%
See 1 more Smart Citation